2001
DOI: 10.1177/00912700122012661
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics of Enalapril in Children and Infants with Hypertension

Abstract: Forty children with hypertension between the age of 2 months and 15 years received 0.07 to 0.14 mg/kg of enalapril as a single daily dose. Enalapril was administered orally as a novel extemporaneous suspension in children younger than 6 years of age and as tablets in older children. First-dose and steady-state pharmacokinetics were estimated in children ages 1 to 24 months, 25 months to < 6 years, 6 to < 12 years, and 12 to < 16 years. Maximum serum concentrations for enalapril occurred approximately 1 hour af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 15 publications
4
44
1
1
Order By: Relevance
“…Debido a ello, debe administrarse dos o tres veces al día, por lo que ha sido sustituido por IECA de acción prolongada 130 , algunos de los cuales se han estudiado recientemente en niños 120 . Por ejemplo, se dispone de resultados de eficacia controlados con placebo para enalapril 131 , fosinopril 132 y lisinopril 133 , y se han llevado a cabo estudios farmacocinéticos para enalapril 134 , lisinopril 135 y quinapril 136 . Si bien los estudios con enalapril 131 y lisinopril 133 han establecido una dosis efectiva mínima de 0,08 mg/kg/día, dosis de 0,6 mg/kg/día fueron bien toleradas.…”
Section: Bloqueadores Betaadrenérgicosunclassified
“…Debido a ello, debe administrarse dos o tres veces al día, por lo que ha sido sustituido por IECA de acción prolongada 130 , algunos de los cuales se han estudiado recientemente en niños 120 . Por ejemplo, se dispone de resultados de eficacia controlados con placebo para enalapril 131 , fosinopril 132 y lisinopril 133 , y se han llevado a cabo estudios farmacocinéticos para enalapril 134 , lisinopril 135 y quinapril 136 . Si bien los estudios con enalapril 131 y lisinopril 133 han establecido una dosis efectiva mínima de 0,08 mg/kg/día, dosis de 0,6 mg/kg/día fueron bien toleradas.…”
Section: Bloqueadores Betaadrenérgicosunclassified
“…While recent reports have described the pharmacokinetics (PK) [5] and dose-response [6] to enalapril in children, similar studies have not been reported with lisinopril. There have been few reported adverse events from lisinopril in pediatric patients, and no clustering of specific adverse events has been observed in children.…”
Section: Introductionmentioning
confidence: 95%
“…The dose of enalapril in children has been reported in a few studies. Wells et al [25] did a comprehensive analysis of the pharmacokinetics of enalapril in children. They used a dosing schedule of 2.5 mg for children less than 28 kg of body weight and 5.0 mg for children greater than 28 kg of body weight, translating to a dosing range of 0.07-0.14 mg/kg.…”
Section: Discussionmentioning
confidence: 99%